Colin Buchanan's American journey. Issue 2 (March 2017) - Ward, Stephen V.
Abstract : In autumn 1962, the British planner Colin Buchanan made an extensive tour of the United States while researching his renowned 1963 report Traffic in Towns, a publication which made him the foremost British planner of his generation. Buchanan was seeking lessons from American experiences that might be applied to Britain, then becoming a mass-motorised society. This paper, which draws on published and unpublished sources, investigates Buchanan's American visit and the part it played in formulating this seminal report. The other, shorter visits to West Germany, Stockholm and Venice are also considered, but briefly, because of the lack of original evidence. By contrast, the main American visit reveals much about Buchanan's attitudes to the United States. It is also a case study of how investigative visits can mobilise urban policy knowledge internationally, showing how positive and negative lessons from such exogenous experiences can inform city and national policy formulation.